Improvement of the thermoelectric properties of a MoO3 monolayer through oxygen vacancies - Zheng, Wenwen; Cao, Wei; Wang, Ziyu; Deng, Huixiong; Shi, Jing; Xiong, Rui (Beilstein Journal of Nanotechnology, 2019)
We have investigated the thermoelectric properties of a pristine MoO3 monolayer and its defective structures with different oxygen vacancies using first-principles methods combined with Boltzmann transport theory. Our results show that the thermoelectric properties of the MoO3 monolayer exhibit an evident anisotropic behavior which is caused by the similar anisotropy of the electrical and thermal conductivity. The thermoelectric materials figure of merit (ZT) value along the x- and the y-axis is 0.72 and 0.08 at 300 K, respectively. Moreover, the creation of oxygen vacancies leads to a sharp peak near the Fermi level in the density of states. This proves to be an effective way to enhance the ZT values of the MoO3 monolayer. The increased ZT values can reach 0.84 (x-axis) and 0.12 (y-axis) at 300 K.
Keywords: Boltzmann transport theory; first-principles calculations; molybdenum trioxides; MoO3 monolayer; oxygen vacancies; thermoelectric properties